The civil rights act and the earnings of lower income Hispanic men in the 1960's - Harriet Duleep; Mark Regets (Institute for the Study of Labor (IZA), 2012)
This paper uses Social Security longitudinal earnings records matched to Current Population Survey data to examine changes in the relative earnings of Hispanic men during a period of dramatic change in public and private policies toward race and ethnicity characterized by, but not limited to, the Civil Rights Act of 1964. Our principle focus is to compare and contrast how lower income Hispanic and African-American men fared during the civil rights era relative to lower-income non-Hispanic whites. Although previous studies have analyzed black economic progress using annual data before and after the Civil Rights Act, this is the first study to do so for Hispanics. We follow a longitudinal sample of individuals who were in the labor market before and after the passage of the Civil Rights Act. Following the same individuals holds constant an array of unmeasured variables such as labor force selectivity and schooling quality that may correlate with the post-1964 period; our approach addresses concerns that the results are the product of changes in these variables. Of particular note - we uncover a significant acceleration following the Civil Rights Act in the relative earnings of low-income Hispanic men.
Keywords: J48; J71; J78; J15; J18; 330; anti-discrimination legislation; minority economic progress; Mexican Americans; Hispanic; low income; Civil Rights Act; longitudinal administrative records; Hispano-Amerikaner; Gleichbehandlungsrecht; Wirkungsanalyse; Einkommen; Niedrigeinkommen; Schätzung; USA